The biology of the South African cliff swallow hirundo spilodera - Earlé, Roy Anthony (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1986)
The general biology of the South African Cliff Swallow Hirundo spilodera was studied over a two year period in the central Orange Free State. This species is highly colonial, nesting mostly on man-made structures such as concrete road bridges. Adult birds were usually faithful to their breeding colony and very few individuals changed colonies. The Cliff Swallow had a surprisingly large vocal repertoire for a swallow and contact calls of the young were individually recognizable. Three species-specific ectoparasites parasitized the Cliff Swallow but none seemed to have a noticeable negative effect on the swallows. Breeding started earlier in larger colonies than in smaller ones and conspecific brood parasitism was a common feature in some colonies. Individual pairs made up to four breeding attempts per season. The findings of this study are compared with the available information on other members of the Hirundinidae and the advantages and costs of Cliff Swallow coloniality are discussed.
Keywords: Hirundo pyrrhonota; Birds -- Breeding -- South Africa; Birds -- Behavior -- South Africa